Analysis of An Inclined Structure Considering Suspension Cables Using Staad.Pro - Rama Devi Kurmi; Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2021)
Seismic analysis is mandatory in every case of structure analysis whether it’s related to any soil condition or geography. Architectures and structure engineers together have created marvels in form of unique structures whether its time from ancient Pyramids to Transamerica Pyramid in San Francisco. This structures are not always about cosmetic interests as even such structures are meant to be stable against different forces and economical aspects. High rise buildings and skyscrapers are designed with different technologies to resist heavy winds and seismic forces and such technologies include leaning at different angles, twisting shapes or creating free shapes for aerodynamics. Many inventions have helped to develop the idea of building tall buildings, the invention of the vertical elevator in 1853 by the American Elisha Graves Otis was one of the most important factors in the development of this concept. Viability of this elevator for quickly vertical movement helped people to move between stories effortlessly. Until 1870, cast iron and wood was the main materials used in construction of building where walls made of masonry had to be so thick in order to be able to carry out the load coming from floors. This system limited the height of the building because of the large weight of its components. Later, the steel frame system was invited which became as the best solution at that time as it much strong system which can tack more load of each floor and therefore the thickness of the walls could be reduced where insulation became its main function. In this investigation, the results of maximum response in terms of base shear, displacement, time history are evaluated. The aim of this research designing and analysis of cable slanted building behavior originated on different sloping angles and its behaviour during earthquake areas of zone V. The seismic analysis of G+12 storey RCC building on varying slope angles is studied and compared with the same on the flat ground. The structural analysis software STAAD Pro V8i is used to study the effect of slant on building performance during earthquake in zone V.
Keywords: Structural System; STAAD.Pro; Slant Buildings; Cable Support System